The Relationship Between Education, Training, and Civil Servant Lecturers Competency - Reimond Hasangapan Mikkael Napitupulu (Journal of Business and Management Review, 2020)
Research Objectives - The purpose of this paper is to discuss conceptual work agreements that discuss the relationship between the following constructs: Education and Training, Commitment of PNS DPK LLDIKTI IV Lecturers in West Java and Banten. Data collection was a survey of a sample of Civil Servant Lecturers in LLDIKTI IV West Java and Banten. Structural equation modeling is used as a tool for analyze hypothetical relationships. Research limitations/ implications - This research is limited to PNS Regional Civil Servant Lecturers IV West Java and Banten, especially Lecturers who have Functional Position Lecturers. While these findings remain valid, they cannot be used for universal generalizations. This study has significant theoretical and implications. Findings - This paper offers original findings through the simultaneous inviting relationship between Education and Training, Competency of PNS Lecturer DPK LLDIKTI IV West Java and Banten